The Relationship between Physical Environment (Temperature and Noise) and Work Fatigue in Gas Station Operators in Pontianak City - Nikola, Ivan; Sunarsieh, Sunarsieh; Saepudin, Malik (JURNAL INFO KESEHATAN, 2024)
Work fatigue is a condition that decreases a person's efficiency and endurance at work. It is caused by many individual and external factors, such as the physical work environment, namely temperature and noise. This study aims to analyze the relationship between the physical environment (temperature and noise) and work fatigue among gas station operator workers in Pontianak City. This research is an analytical observational research with a cross-sectional approach. The population in this study was 147 gas station operator workers in Pontianak City, and the total sample was 60 respondents. The data analysis techniques used are univariate and bivariate analysis, and the Chi-Square statistical test was used for bivariate analysis. The research results show the relationship between temperature and work fatigue in gas station operator workers, with a value of p=0.003 and OR=10.286 (CI=1.940-54.527). There is also a relationship between noise and work fatigue in gas station operator workers, with a value of p=0.042 and OR=6.750 (CI=1.227-37.142). The conclusion is a relationship exists between temperature and noise and work fatigue among gas station operator workers in Pontianak City. This research advises that gas station operator workers are expected to consume sufficient drinking water while working, at least one glass of 250ml every 20-30 minutes or 2.8 liters/day, and can add a little salt to drinking water to avoid harmful effects such as dehydration. To reduce noise, you should use ear PPE, such as earplugs.